Dual energy computed tomography: a novel technique for diagnosis of gout. (29th April 2016) - Ahmad, Zohra; Gupta, Arun Kumar; Sharma, Raju; Bhalla, Ashu Seith; Kumar, Uma; Sreenivas, V.
Abstract: Aim: To evaluate the sensitivity and specificity of dual energy computed tomography (DECT) for diagnosing gout compared with a composite gold standard (CGS) comprising joint aspiration and/or American College of Rheumatology clinico‐radiographic criteria. Methods: Ninety patients of suspected gout underwent radiography and DECT of bilateral feet and knees. Radiographs and non‐contrast CT (NCCT) were assessed for morphological characteristics, following which DECT was used to identify urate deposits. Results: With CGS as a reference ( n = 90), sensitivity of radiographs was 15% (95% confidence interval [CI]: 6–27%) while specificity was 100% (95% CI: 90–100%). Sensitivity of NCCT was 26% (95% CI: 15–40%) while specificity was 97% (95% CI: 85–99%). Sensitivity of DECT was 82% (95% CI: 68–90%) while specificity was 89% (95% CI: 73–96%). Fifty‐five patients underwent joint aspiration. Sensitivity and specificity of radiographs and NCCT with aspiration as a reference ( n = 55) were not much different from that of CGS. However, DECT showed a higher sensitivity of 100% (95% CI: 86–100%) and a lower specificity of 48% (95%CI: 28–68%) with aspiration alone. Conclusions: Dual energy computed tomography had higher sensitivity compared to conventional imaging with CGS as a reference; however, its specificity dropped with aspiration as a reference. It may be a useful adjunct for the diagnosis of gout, especially in the acute and inter‐critical stage.